Pengaruh Current Ratio, Debt to Equity Ratio, Return on Asset Terhadap Kebijakan Dividen Pada Perusahaan Manufaktur Yang Terdaftar Di Bursa Efek Indonesia - Dinda Fauzia Aulia; Zufrizal Harahap; Jalilah Ilmiha; Shofwan Andri; Abdul Rasyid (JRAM (Jurnal Riset Akuntansi Multiparadigma), 2022)
Manufacturing companies are part of companies that contribute to the Indonesian economy. This company has become the object of investors in investing because it is able to grow rapidly in economic development and has a large scope and market share. This study aims to determine the effect of the Current Ratio, Debt to Equity Ratio, Return on Assets on the dividend policy of manufacturing companies in the food beverage sub-sector listed on the Indonesia Stock Exchange in 2018-2019. This study uses 15 manufacturing companies in the consumer goods industry sector. The sampling technique in this study is a purposive sampling technique. The data analysis technique in this study used multiple linear regression with the help of the SPSS program. The results showed that the variable current ratio, debt to equity ratio and return on assets have an effect on dividend policy in manufacturing companies listed on the Indonesia Stock Exchange.